SOCIOLINGUISTICS IS A LINK BETWEEN SOCIOLOGY AND LINGUISTICS. - Nasirova, M (Журнал иностранных языков и лингвистики, 2021)
This paper investigates introduction to sociolinguistics of the English language. The main purpose of this article is to review the scientifically important theoretical points of sociolinguistics, examines the sociolinguistic works of authors who have examined the English language.